Decision Making in a Case of Multiple Sclerosis — Preliminary Note - John, I. Balla (Methods of Information in Medicine, 1981)
Decision making was studied in a case of multiple sclerosis with the aim of understanding what sort of decision rules may be used to accept the final hypothesis in coming to a diagnosis. 17 persons, including 4 expert neurologists, 1 senior resident and 12 medical students interviewed a simulated patient.It was found that the final hypothesis depended on the examination of a relatively small number of aspects (clinical features). Little search was made for aspects of choice alternatives other than the favoured one, namely multiple sclerosis. The results thus did not support pattern recognition as being important in decision making, and one may speculate that elimination by aspect or simple dominance rules may have been used in this case. The findings emphasise the apparent need to look for important distinguishing criteria in coming to a diagnosis.This may have significant implications for medical education in that students may have to concentrate on learning heavily weighted distinguishing cues rather than long lists of individual clinical features of diseases.
Keywords: Decision Making; Multiple Sclerosis; Simulation